2004
DOI: 10.1177/002204260403400201
|View full text |Cite
|
Sign up to set email alerts
|

The Health Benefits of Secondary Syringe Exchange

Abstract: From a process evaluation, participants in San Francisco's syringe exchange program (SEP) are described. Three groups, primary, secondary, and nonexchangers, were interviewed for a total of 244 study participants recruited from eight needle exchange sessions. Fifty percent of all primary exchangers exchanged for one or more injecting drug user(s) (IDUs). Three general routes of syringe distribution were identified between primary and secondary exchangers: between close friends and lovers; for people who lived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 41 publications
(9 reference statements)
3
27
0
Order By: Relevance
“…Data collection included participant observation, indepth life history interviews, and a closed-ended quantitative instrument. Data collection was completed in 1995 with a total of 244 exchange participants (clients of the syringe-exchange program) recruited from eight syringeexchange sites, many of whom exchanged needles for other users unable or unwilling to visit the exchange (Kelley, Murphy, & Lune, 2001;Murphy, Kelley, & Lune, 2004). Data collection also included interviews with 56 volunteer service providers, which represented the total population of providers involved at the eight data collection sites during the time of our study.…”
Section: Methodsmentioning
confidence: 99%
“…Data collection included participant observation, indepth life history interviews, and a closed-ended quantitative instrument. Data collection was completed in 1995 with a total of 244 exchange participants (clients of the syringe-exchange program) recruited from eight syringeexchange sites, many of whom exchanged needles for other users unable or unwilling to visit the exchange (Kelley, Murphy, & Lune, 2001;Murphy, Kelley, & Lune, 2004). Data collection also included interviews with 56 volunteer service providers, which represented the total population of providers involved at the eight data collection sites during the time of our study.…”
Section: Methodsmentioning
confidence: 99%
“…Most research confirms that SSE occurs more frequently within established injecting networks, such as among close friends, sexual partners, and family members. 10,13 Furthermore, IDUs with larger injecting networks, those living in close proximity to each other, and those who exchange drugs have also been found to participate in SSE. 13,31 An Australian study showed the importance of one's personal network as a source of injecting equipment, both used and clean.…”
Section: G0001mentioning
confidence: 99%
“…7 The high volume of syringes distributed through SSE reflects findings from other jurisdictions where SSE providers have been reported to distribute up to 60% of syringes exchanged at SEPs, although these individuals represented less than 10% of the clientele. 8,13 Traditional SEP and pharmacy-based syringe distribution strategies have several limitations. The use of SEPs may be restricted by limited hours of operation, distribution policies, geographic distance to the SEP, fear of stigmatization, as well as fear of police harassment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations